Kemahiran Berkomunikasi Lisan dalam Konteks Instruksional Guru Sekolah Dasar - Suparno Suparno (Universitas Negeri Malang, 2016)
This research was conducted to describe the oral communication skill in the instructional context of primary school teachers of East Java. An evaluative-survey design was implemented in this study. The sample consisted of 120 teachers from four Karesidenans of East Java selected by area sampling. Data were gathered by observations and recording. The mean measures, analysis of variance and t-test were used to analyze the data. The results indicated that the oral communication skill in the instructional context of primary school teachers was unsatisfactory. In certain aspects there were differences in the level of the skill among subject matters and also between urban and rural teachers. The skill of urban teachers was higher than the skill of rural teachers